1976
DOI: 10.1111/j.1600-0714.1976.tb01755.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro metabolism of testosterone‐4‐14C by canine salivary glands

Abstract: Abstract. Testosterone‐4‐14C (2430 pmol, 0.48 μM) was incubated aerobically in 67 mM phosphate buffer pH 7.4 with homogenates and minces of salivary glands from male dogs. Extracted radiosteroids were resolved by thin‐layer chromatography on silica gel, removed and quantitated. Substantially higher NAD+‐dependent 17 β‐hydroxy‐C19‐steroid oxidoreductase activity was found in submaxillary gland homogenates than in similar parotid‐gland preparations. Preliminary evidence is presented that the enzyme activity per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1977
1977
1990
1990

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Furthermore, in the present work [7a-3H]androstenedione was converted to testosterone, thus demonstrating the presence of 17/?-hydroxysteroid dehydrogenase which has previously been found in the salivary glands of the pig (Kadis & Chyn, 1975) and of other species, e.g. rat and mouse (Baldi & Charreau, 1972), rabbit and man (Cardinali, Denari & Rosner, 1971), man (ElAttar, 1974) and dog (Mosadomi & Ofner, 1976). However, the finding that 3H-labelled DHA and androstenedione were converted to relatively large yields of 5a-androstane-3,17-dione and androsterone indicates that the submaxillary gland of the boar also has the capacity to limit the production of potent androgens.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, in the present work [7a-3H]androstenedione was converted to testosterone, thus demonstrating the presence of 17/?-hydroxysteroid dehydrogenase which has previously been found in the salivary glands of the pig (Kadis & Chyn, 1975) and of other species, e.g. rat and mouse (Baldi & Charreau, 1972), rabbit and man (Cardinali, Denari & Rosner, 1971), man (ElAttar, 1974) and dog (Mosadomi & Ofner, 1976). However, the finding that 3H-labelled DHA and androstenedione were converted to relatively large yields of 5a-androstane-3,17-dione and androsterone indicates that the submaxillary gland of the boar also has the capacity to limit the production of potent androgens.…”
Section: Discussionsupporting
confidence: 85%
“…It is suggested that when testosterone is metabolized primarily to androstenedione as in the submaxillary gland of the dog (Mosadomi & Ofner, 1976) and the rat (Baldi & Charreau, 1972), that the gland in these species is not a significant androgen target organ, and morphological observations tend to support this hypothesis. How¬ ever, when testosterone is primarily reduced to 5<x-products with retention of the 17/?-hydroxy group, this is usually associated with tissues which are known to be a target for androgens (Baulieu, Lasnitzki & Robel, 1968;Ofner, Leav & Cavazos, 1974).…”
Section: Discussionmentioning
confidence: 99%